2014
DOI: 10.1038/ki.2014.95
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the angiotensin II type 1 receptor–associated protein enhances renal sodium reabsorption and exacerbates angiotensin II–mediated hypertension

Abstract: Angiotensin II type 1 receptor (AT1R)–associated protein (ATRAP) promotes AT1R internalization along with suppression of pathological activation of tissue AT1R signaling. However, the functional significance of ATRAP in renal sodium handling and blood pressure regulation under pathological stimuli is not fully resolved. Here we show the blood pressure of mice with a gene-targeted disruption of ATRAP was comparable to that of wild-type mice at baseline. However, in ATRAP-knockout mice, angiotensin II–induced hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 66 publications
4
43
0
Order By: Relevance
“…Our work indicates that NO inhibition induces the overexpression of AT1R in the kidney, contributing to hypertension and renal damage. Ohsawa et al [31] have shown that renal AT1R activation promotes sodium retention via ENaC activation, and consecutively the exacerbation of hypertension induced by Ang II administration.…”
Section: Discussionmentioning
confidence: 99%
“…Our work indicates that NO inhibition induces the overexpression of AT1R in the kidney, contributing to hypertension and renal damage. Ohsawa et al [31] have shown that renal AT1R activation promotes sodium retention via ENaC activation, and consecutively the exacerbation of hypertension induced by Ang II administration.…”
Section: Discussionmentioning
confidence: 99%
“…ATRAP‐KO mice generated on a C57BL/6 background by targeted gene disruption were used in the study . All experiments were performed with age‐matched ATRAP‐KO mice and WT mice (3–4, 11–12, and 22–25 months old; n=6–11 in each group).…”
Section: Methodsmentioning
confidence: 99%
“…Histological analysis was performed as described previously . The heart, aorta, and kidney were fixed with 4% PFA and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATRAP deficiency exacerbated angiotensin-II-mediated hypertension by pathological activation of renal tubular AT1R. This directly stimulates ENaC in the distal tubules and enhances sodium retention in an aldosterone-independent manner while NCC seems not to be implicated in this mechanism [66 ].…”
Section: Enac Regulation By Renin-angiotensinaldosterone System (Raas)mentioning
confidence: 98%